Petrology and oxygen isotopic composition of large igneous inclusions in ordinary chondrites: Early solar system igneous processes and oxygen reservoirs. (1st December 2019) - Ruzicka, Alex M.; Greenwood, Richard C.; Armstrong, Katherine; Schepker, Kristy L.; Franchi, Ian A.
Abstract: Large (>3.5 mm and up to 4 cm across) igneous inclusions poor in metal and sulfide are a minor but not uncommon component in ordinary chondrites, and have implications for the nature of physiochemical and melting processes in the early solar system. We obtained petrographic-chemical data for forty-two large igneous inclusions in ordinary chondrites of various groups (H, L, LL) and petrographic types (3–6) and oxygen isotope data for a subset of twelve of these inclusions and their host chondrites. Different inclusions formed both before and after the thermal metamorphism experienced by their host chondrites. The bulk chemical compositions of the inclusions vary broadly around whole-rock chondrite composition, comprise four main chemical types and some other variants, and show little evidence of having formed as igneous differentiates. Oxygen isotope compositions overlap ordinary chondrite compositions and are related to inclusion chemical type. Most prevalent in type 3 and 4 chondrites are inclusions, often droplets, of the vapor-fractionated ( Vfr ) chemical type, either enriched in refractory lithophile elements, or depleted in volatile lithophile elements, or both. These inclusions have low Δ 17 O (∼0.1–0.6‰) and high δ 18 O (∼4–8‰) values and formed in reservoirs with Δ 17 O lower than their hosts, primarily as evaporative melts and mixtures that probably experienced kinetic isotopic fractionation. Another chemical type ( Unfr + K ) has unfractionated abundances of lithophile elements except for being strongly enriched in K, a signature also found in some impact melts from melt rocks and melt breccias. These inclusions formed by impact melting of chondritic material and accompanying K enrichment. Inclusions with unfractionated ( Unfr ) lithophile element abundances are present in type 3–6 chondrites and are prevalent in type 5 and 6. Some are spatially associated with coarse metal-sulfide nodules in the chondrites and likely formed by in situ impact melting. Others were melted prior to thermal metamorphism and were chemically but not isotopically homogenized during metamorphism; they are xenoliths that formed in oxygen reservoirs different than the hosts in which they were metamorphosed. The latter inclusions provide evidence for nebular or collisional mixing of primitive materials prior to thermal metamorphism of asteroid bodies, including transport of H-like source materials to the L body, LL-like source materials to the L body, and low-Δ 17 O materials to the LL body. Feldspar-rich ( FldR ) inclusions have compositions similar to melt pockets and could have formed by disequilibrium melting and concentration of feldspar during an impact event to form large droplets or large masses. Overall, the results of this study point to important and varied roles for both "planetary" impact melting and "nebular" evaporative melting processes to form different large igneous inclusions in ordinary chondrites. Chondrules may have formed by processes similar to those inferred for large inclusions, but there are important differences in the populations of these objects.